Consequences of Assessment: What is the Evidence? - Mehrens, William A. (Education Policy Analysis Archives, 1998)
Attention is here directed toward the prevalence of large scale assessments (focusing primarily on state assessments). I examine the purposes of these assessment programs; enumerate both potential dangers and benefits of such assessments; investigate what the research evidence says about assessment consequences (including a discussion of the quality of the evidence); discuss how to evaluate whether the consequences are good or bad; present some ideas about what variables may influence the probabilities for good or bad consequences; and present some tentative conclusions about the whole issue of the consequences of assessment and the amount of evidence available and needed.